Deep Neck Infections: The Effectiveness of Therapeutic Management and Bacteriological Profile - Geanina Bandol; Mihail Dan Cobzeanu; Mihaela Moscalu; Octavian Dragos Palade; Liliana Moisii; Florentina Severin; Emilia Patrascanu; Florin Mocanu; Andrei Ionut Roman; Bogdan Mihail Cobzeanu (Medicina)
Background and Objectives: Deep neck infections (DNIs) are severe diagnoses that can cause serious complications. However, there are insufficient data to predict the evolution of this pathology. This study aims to review the microbiology of DNIs and to identify the factors that influence prolonged hospitalization. Materials and Methods: The present retrospective cohort observational analytical study analyzed 138 patients with DNIs who were diagnosed and received surgical treatment over a 8-year period. Results: Reduced lymphocyte percentages and increased neutrophil-to-lymphocyte ratios (NLRs) were significantly associated with complications (p < 0.001 and p = 0.0041, respectively). Laryngotracheal infections were significantly associated with complications (25.53%) (p = 0.0004). Diabetes mellitus (DM) and immunocompromised status were strongly associated with complications (p < 0.001 and p = 0.0056, respectively), establishing these conditions as significant risk factors. Patients with complications experienced substantially longer hospitalizations, with a mean duration of 24.9 days compared to 8.32 days in patients without complications (p < 0.001). Complications were observed in 47 patients (34.06%). The most common complications were airway obstruction, which occurred in 26 patients (18.84%), and mediastinitis, which was noted in 31 patients (22.46%). Patients requiring tracheotomy due to airway obstruction had 6.51 times higher odds of long-term hospitalization compared to those without airway obstruction (OR = 6.51; p < 0.001). Mediastinitis was associated with a 4.81-fold increase in the odds of prolonged hospitalization (OR = 4.81; p < 0.001). Monomicrobial infections were observed in 35.5% of cases, with no significant difference between the short-term (<2 weeks, 37.33%) and long-term (≥2 weeks, 33.33%) hospitalization groups (p = 0.8472). Conversely, polymicrobial infections were significantly associated with prolonged hospitalization, occurring in 20.63% of the long-term cases compared to 6.66% of the short-term cases (p < 0.001). The most common aerobic bacteria observed were Staphylococcus aureus (14.28%), Streptococcus constellatus (12.69%) and Streptococcus viridans (7.93%) during long-term hospitalization. Comparative analysis of the Kaplan–Meier survival curves based on the presence of infection revealed a significantly lower survival in cases with a positive culture. Conclusions: Deep neck infection has a complex pathology, whose therapeutic management remains a challenge in order to reduce the length of hospitalization and mortality.